Pengaruh Brand Ambassador Idol Korea Dalam Mempromosikan Produk Serta Dampaknya Terhadap Keputusan Dan Minat Pembelian Di Indonesia (Literatur Review) - Susi Arijanti; Imam Jayanto; Retnoning Ambarwati (Jurnal Bisnis dan Manajemen West Science, 2023)
The purpose of this research is to find out the influence of Korean idol brand ambassadors in promoting products and thei impact on purchasing decisions and interests in Indonesia. Brand Ambassador is a person who is invited by the company to became an icon or “Face” of a brand or product. Brand Ambassador is usually a person from an influential circle that can have an impact oh the community. The method used using the Google Scholar database. Then obtained 8 articles to be analyzed and reviewed. The result of this research is that Brand Ambassador Idol Korea isa influential in promoting and also influences the interest anf purchashing decisions.